Relation between soil solution composition and petiole cellular extract of crops in western Mexico - Benavides-Mendoza, Adalberto; de Alba-Romenus, Karim; Francisco-Francisco, Nazario (REVISTA TERRA LATINOAMERICANA, 2021)
Crop fertilization greatly impacts food production. However, insufficient applications can lead to poor yields. On the other hand, an excessive application leads to soil and aquifers pollution. In this paper, field studies were carried out to determine the ranges of mineral concentration and the interaction of the ions in the soil solution (SS) and the petiole cellular extract (PCE) in several cultures established in the states of Guanajuato, Colima and Jalisco, Mexico. The hypothesis states that there is a causal relationship between the mineral composition of the soil solution (SS) and the minerals and total soluble solids (TSS) in petiole cellular extract (PCE). The following cultures were studied in this research: avocado, blueberry, broccoli, cauliflower, raspberry, strawberry, lettuce, cantaloupe, papaya, and pepper. For each culture, PCE samples and SS samples using a press to break tissue and ceramic tip lysimeters were obtained. The results were processed to obtain ranges of variation within 50% of the closest values to the median. Correlations between the several ion concentrations were analyzed using analysis of variance. The results showed values (mg L-1) of NO3- (40-620), PO43- (17-66), K+ (3-377), Ca2+ (27-582), Na+ (15.3-500), Mg2+ (10-53), Fe3+ (0.6‑1.8), and Zn2+ (2.8-7.4) in soil solution, which allowed obtaining values of NO3- (27-9225), K+ (820-9375), Ca2+ (1.0-650), Na+ (25-620) and TSS (2-13 °Brix) in petiole cellular extract of petiole. Statistically significant correlations were observed between the concentrations of the SS ions regarding the concentrations in PCE in crops suggesting a relationship between the plant nutritive assimilation and cations or anions present in soil solution. The conclusion derived from this study is that ionic concentration ranges registered in the SS and in the PCE provide an approximation to the ranges of nutritional sufficiency for the horticultural crops established in the summer-winter in western Mexico.